(untitled) (Journal of Fatima Jinnah Medical University, 2025)
Background: Knee injuries like medial meniscal tears impair mobility. Magnetic Resonance Imaging (MRI) is the gold standard but costly and less accessible. This study evaluates ultrasound’s predictive accuracy as a more affordable, real-time, non-invasive alternative to MRI. The objective of this study was to find out predictive accuracy of ultrasound to detect medial meniscal tear in patients presenting with knee injuries taking MRI as gold standard. Methods: The study at Sir Ganga Ram Hospital enrolled 100 knee injury patients over six months w.e.f. March to August, 2021 using non-probability purposive sampling as per inclusion criteria. Patients underwent ultrasound with a 7.5 MHz transducer and MRI with a 1.5 T machine. Radiologists were blinded to each other’s findings. Data were analyzed using SPSS to calculate ultrasound’s sensitivity, specificity, predictive values, and accuracy against MRI as the gold standard. Results: Ultrasound detected medial meniscal tears in 83% of patients, predominantly in the posterior zone (80%). MRI showed similar findings, with 85% posterior zone tears. Comparing ultrasound to MRI, ultrasound demonstrated high diagnostic performance: sensitivity of 94.67%, specificity of 93.33%, and overall accuracy of 95.94%. The positive predictive value was 98.60%, and the negative predictive value was 84.41%, indicating ultrasound is a reliable tool for detecting medial meniscal tears. Conclusions: Ultrasound showed 96% accuracy in detecting medial meniscal tears, slightly less than MRI, which had higher sensitivity and specificity. However, ultrasound remains a useful, non-invasive option when MRI is unavailable or contraindicated.